Political Marketing and Management in the 2020 New Zealand General Election
XIV, 186 p. 39 illus., 3 illus. in color.
Keywords: This book is the second volume in the Palgrave Studies in Political Marketing and Management series to focus on political marketing and management in New Zealand’s general elections. Co-edited by political marketing experts Edward Elder and Jennifer Lees-Marshment from the University of Auckland, and with contributions from academics and practitioners, this book covers topics including political strategy, Vote Compass, market research, political branding, delivery marketing, targeting and political communication. Importantly, this book looks at the use of political marketing and management during a global health crisis, the COVID-19 pandemic. In doing so, this book provides valuable insights into political marketing and management in practice, not just for New Zealand, but for political leaders, parties and campaigners around the world. Edward Elder is Professional Teaching Fellow in the Faculty of Arts at the University of Auckland, NewZealand. Jennifer Lees-Marshment is Associate Professor in Politics and International Relations at the University of Auckland, New Zealand.